An online monitoring method of moisture in transformer bushings based on an improved humidity indicator card. Issue 6 (7th December 2021) - Shu, Shengwen; Zheng, Zhicong; Chen, Yangyang; Li, Wei; Wang, Guobin; Liao, Fuwang
Abstract: One of the main reasons for the failure of transformer bushings is moisture penetration. Here, an online monitoring method of moisture in transformer bushings based on an improved humidity indicator card, which belongs to the group of passive physical and chemical monitoring methods, is proposed. First, the operating principles and monitoring system are explained. Next, by means of a moisture simulation device, the moisture migration characteristics between the gas and oil, the influence of the interface radius on the response characteristics of the monitoring device, and the characteristics of the humidity indicator card are studied experimentally. Then, the moisture migration process in micro‐scale is simulated by molecular dynamics simulation. Finally, by changing the mass fraction of the cobalt chloride in the humidity card, the warning values of relative humidity at different temperatures are obtained. The simulation results show that water molecules can migrate from the oil–paper system to the air. Moreover, once the moisture enters the transformer bushing, the proposed humidity indicator card can correctly display the relative humidity at different temperatures. In conclusion, the proposed method provides a new way for online moisture monitoring of transformer bushings.